Quelques ficelles de sociologie carcérale - Corinne Rostaing (Criminocorpus)
Based on the experience of various long-term ethnographic surveys carried out on the prison world, this article questions prison as a ground of inquiry. It is not a matter of drawing up the litany of the difficulties that a research in prison may be confronted with, but of telling as precisely as possible the ways of actually making the field in prison, or even of drawing some "tricks of the trade " (H.S. Becker, 2002).The article first proposes to discuss the qualifiers associated with this environment. Is it difficult field since it is closed and under surveillance? Is it a minefield, in the sense that the opacity of the prison world raises many obstacles to the investigation, where the antagonisms that cross it make it more necessary to specify its posture and where the situation of disqualification of the inmates requires to re-establish a semblance of symmetry?The prison field subjects classical methods to extreme conditions. These methods need to be adapted and even rethought in this specific context. But above all, sociological practice is upset by moral dilemmas, such as being confronted with justice and crimes, having to maintain its independence despite the hierarchy of credibility, or resisting the temptation to denounce Confrontation with deprivation of liberty and unworthy situations.